2017
DOI: 10.3126/jnps.v36i3.12155
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Evaluation of Neonates with Hyperbilirubinemia by Otoacoustic Emissions and Brain Stem Evoked Response Audiometry

Abstract: Introduction: Neonatal hyperbilirubinemia is one of the most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…13, 28 Furthermore, preterm infants with TSB levels equal to or above 14 mg/dl have been reported to have a higher risk of deafness. 20 Mirajkar and Rajadhyaksha 15 also found persistent abnormal ABR in infants who retrospectively had TSB levels between 12 and 15 mg/dl when they were screened before 3 months of age, whereas none of those with TSB levels above 25 mg/dl had abnormal ABR findings at follow-up. Since it may be difficult to eliminate all other risk factors for hearing loss in hospitalized newborns with hyperbilirubinemia, as seen in our study, the foregoing suggests that hyperbilirubinemia alone may not be responsible for the hearing test abnormalities observed, as opined by some authors.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…13, 28 Furthermore, preterm infants with TSB levels equal to or above 14 mg/dl have been reported to have a higher risk of deafness. 20 Mirajkar and Rajadhyaksha 15 also found persistent abnormal ABR in infants who retrospectively had TSB levels between 12 and 15 mg/dl when they were screened before 3 months of age, whereas none of those with TSB levels above 25 mg/dl had abnormal ABR findings at follow-up. Since it may be difficult to eliminate all other risk factors for hearing loss in hospitalized newborns with hyperbilirubinemia, as seen in our study, the foregoing suggests that hyperbilirubinemia alone may not be responsible for the hearing test abnormalities observed, as opined by some authors.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, persistent brainstem auditory evoked response (BAER) abnormalities were reported among term newborns with TSB less than 15 mg/dl. 14, 15 These reports suggest that the specific bilirubin level at which hearing becomes impaired is ill-defined. Furthermore, in 2015, Corujo-Santana et al 16 reported hearing loss in 13 preterm and two term newborns with bilirubin levels of 5−13.99 mg/dl, while 11 preterm and five term newborns had hearing loss at bilirubin levels of 14 to 19.99 mg/dl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, eight studies reported aBAERS among neonates admitted with jaundice (Figure 7). [6,33,34,39,45,64,87,89,91].…”
Section: Resultsmentioning
confidence: 99%
“…The funnel plot appeared largely asymmetrical (Figure 8) with empirical evidence supporting this observation (Begg test p < 0.001, Egger's bias = 13.0, p < 0.001). [6,33,34,39,45,64,87,89,91].…”
Section: Resultsmentioning
confidence: 99%